공간적 자기상관을 활용한 건물부문 온실가스 배출량의 공간적 분포특성과 변화에 관한 연구: 경기도 성남시를 중심으로 - 여관현(Yeo, Kwan Hyun) (한국기후변화학회지, 2024)
This study analyzes the changes in spatial patterns and spatial distribution characteristics of greenhouse gas emissions in the building sector in 2013 and 2023 and suggests implications. The data for this study were constructed by attribute joining individual public notice land prices and energy consumption data (electricity and gas) in the building sector with spatial attribute data. In addition, greenhouse gas emissions by plot for 2013 and 2023 were calculated. The LISA analysis using the local Moran index and hotspot analysis using Getis Ord's statistics were performed. Greenhouse gas emissions tended to cluster around Bundang-gu, a new city, and the amount of greenhouse gas emissions increased sharply in the old downtown area (Sangdaewon 1-dong, Sinchon-dong, and Bukjeong-dong) over the past 10 years. Hotspot analysis, similar to the LISA analysis, identified the old downtown area (Sangdaewon 1-dong, Sinchon-dong, and Bukjeong-dong) as a hotspot with high carbon emissions. Three hotspot areas (Yatap-dong, Sunae-dong, and Gumi-dong areas) were observed in 2013, while seven hotspot areas were noted in 2023, with the addition of Sangdaewon 1-dong, Sampyeong-dong, Baekhyeon-dong, and Jeongja-dong to the existing three. KCI Citation Count: 0